Experience with Empirical Treatment of Severe Acute Respiratory Syndrome Due to Coronavirus, Genotype IV - V. N. Shchukina; S. Ya. Loginova; S. V. Borisevich; V. P. Bondarev (Антибиотики и Химиотерапия, 2020)
Foreign experience with empirical management of severe acute respiratory syndrome (SARS) due to coronavirus, genotype IV is described. It is indicated that the data on the efficacy of ribavirin with respect to SARS in the patients are contradictory. The efficacy of two chemotherapeutics, i. e. lopinavir and ritonavir used in the SARS foci is confirmed. The drugs are at present applicable all over the world in retrovirus therapy of HIV infected subjects. The search for efficient Russian unspecific medicines for control of SARS is actual.